Gradiente vertical de decomposição e dinâmica da água no mulch de cana-de-açúcar afetados pela quantidade de palha - Dietrich, Guilherme (2018)
The partial removal of sugarcane straw (Saccharum spp. L.) from the soil surface after mechanized harvesting for the production of cellulosic ethanol leaves different mulch thicknesses at the soil surface. Thus, the need arises to know the amount of straw to be harvested without harming the soil conservation. The objective of the present study was to understand how the thickness of the mulch, which varies according to the amount of straw, and the nitrogen fertilization (N) affect the water dynamics and the decomposition of the mulch and the layers that compose it, as the thickness of the mulch affects the water content and the soil temperature for one year. The contribution of equivalent amounts to 0, 4, 8 and 12 DM ha-1 of straw (S), on a dry basis, with and without N, was carried out inside screened frames and left on the soil surface after harvest, in Santa Maria, RS, under subtropical climate. Furthermore, the 8S and 12S treatments were divided into top (T) and lower (L) layers and T, medium (M) and L layer of straw, respectively, and stacked in order to reconstitute the amounts of straw. The 4S treatment was considered T and L. The layers were separated by a synthetic mesh of 10 mm and sampled separately. The main analyzes carried out on straw and mulch were: moisture, carbon and nitrogen remaining (CR and NR). For the soil, the temperature and the water content were evaluated using WCR probes (CS 616 model) and T-type copper-constantan thermocouple sensors, respectively. The results showed that the mulch and N thickness did not affect the decomposition and the release of N. The moisture of the mulch increased according to the initial amount of straw, but did not reflect the degradation of the mulch (67%, on average). The different amounts of straw did not differ in the rates of decomposition because there is a compensatory effect between the layers. The lower proportion of straw in contact with the soil was compensated by higher rates of decomposition of the lower layer. Among the mulch layers, the water content and decomposition rate differed according to the position (L> M> T). The top layers presented the same humidity and decomposition rate for the three treatments. On the other hand, the lower layers decomposed more rapidly under larger quantities of straw, which also reflected in moisture (12S L> 8S M> 4S L). The remaining N showed similar behavior to C. The mulch 8S and 12S presented higher average water content and lower average soil temperature compared to the 0S and 4S mulches. Finally, this work shows that the dynamics of mulch decomposition is governed mainly by the dynamics of the water, which in turn is affected by mulch thickness, vegetative canopy cover and local weather conditions.